Evaluation Treated of Marginal Resection Followed by Non-Vascularized Fibular Grafts in Ameloblastoma of Mandible: A Case Series - Daru Cahayadi, Sigit; Adhitya Suyatno, Aria (American Scientific Research Journal for Engineering, Technology, and Sciences, 2019)
Introduction Ameloblastoma is a rare odontogenic tumour of the mandible and maxilla. Although, reconstruction with free flaps remains gold standard, many factors must be considered in this method including the need of surgical expertise and equipment, increased intra operative time, post-operative stay and socioeconomic reasons. Non-vascularized bone grafts from the fibula offers many advantages and could be an alternative method. Method This case series will present two cases of ameloblastoma treated with radical resection followed by NVFG reconstruction. Information was obtained through patient follow-up, and medical record. Outcome evaluation will be revealed and discussed. Result The patients were 44 y.o. male and 25 y.o. female. There was no serious complication found due to operation such as infection and wound dehiscence in both patients. A month after surgery, the lump is still existed but only consist of soft tissue swelling. Despite the full normal function have not return yet, the basic function of jaw such as swallowing, and mouth opening are good. Radiological finding a month after operation shows little callus formation in both patients. Discussion The radical surgical option is the current standard of care for ameloblastoma while not many studies have been conducted to compare vascularized and non-vascularized bone reconstruction. NVFG can provide a better quantity of bone to replace implants and a more satisfactory contour than vascularized graft. However, NVFG will undergo remodelling process after reconstruction, therefore implant placement would end in failure if inserted too early when the remodelling process has not finished. Vascularized bone graft is indicated in radiation patients while non-vascularized graft is used in non-radiation patients. A good functional outcome and least donor morbidity could be seen in our patient undergone NVFG reconstruction after radical resection. NVFG is a good alternative in small segmental defect after resection of ameloblastoma of the mandible.